MASKULINITAS PEREMPUAN DALAM GOKUSEN KARYA KOZUEKO MORIMOTO - , DIANA PUSPITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Masculinity is the construction of gender identity generally applied to men, but not all men will automatically be deemed masculine